Distribution of GABAergic Neurons and VGluT1 and VGAT Immunoreactive Boutons in the Ferret (Mustela putorius) Piriform Cortex and Endopiriform Nucleus. Comparison With Visual Areas 17, 18 and 19 - Navarro, Daniela; Alvarado, Mayvi; Figueroa, Alejandra; Gonzalez-Liencres, Cristina; Salas-Lucia, Federico; Pacheco, Pablo; Sanchez-Vives, Maria V.; Berbel, Pere (Frontiers in Neuroanatomy, 2019)
We studied the cellular organization of the piriform network (comprising the piriform cortex and endopiriform nucleus) of the ferret (Mustela putorius) -a highly excitable region prone to seizures- and, more specifically, the distribution and morphology of different types of GABAergic neurons, and the distribution and ratio of glutamatergic and GABAergic boutons, and we compared our findings to those in primary visual area 17, and secondary areas 18 and 19. We accomplished this by using cytochrome oxidase and immunohistochemistry for mature neuronal nuclei (NeuN), GABAergic neurons (glutamic acid decarboxylase-67, calretinin and parvalbumin), and for excitatory (vesicular glutamate transporter 1; VGluT1) and inhibitory (vesicular GABA transporter; VGAT) boutons. In the ferret, the cellular organization of the piriform network is similar to that described in other species such as cats, rats and opossums although some differences also exist. GABAergic immunolabeling showed similarities between cortical layers I-III of the piriform cortex and visual areas, such as the relative distribution of GABAergic neurons and the density and area of VGluT1- and VGAT-immunoreactive boutons. However, multiple differences between the piriform network and visual areas (layers I-VI) were found, such as the percentage of GABAergic neurons with respect to the total number of neurons and the ratio of VGluT1- and VGAT-immunoreactive boutons. These findings are relevant to better understand the high excitability of the piriform network.